Pembuatan Pakan Ikan bagi Kelompok Tani Desa Wangen Lamongan Guna Meningkatkan Pengetahuan dan Kemandirian Budidaya Ikan - Eko Sutrisno; Lovi Sandra; Mohammad Muslimin; Ramli Ramli; Nuril Ahmad; Raida Amelia Ifadah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The majority of Wangen Village residents make a living as pond farmers. Cultivation carried out are vannamei shrimp, milkfish, sombro, carp and mujair. The obstacle faced by the residents of Wangen Village is the high price of fish seeds and feed, thereby reducing profits and even many who experience losses due to changes in weather or bacterial attacks in ponds. In order to reduce dependence on fish feed from manufacturers, training activities for making fish feed are needed so as to reduce production costs Methodology: The community dedication was carried out in Wangen Village, Glagah Lamongan District with 28 participants on Saturday 18 June 2022. The implementation of community service was carried out in three stages, namely planning, implementation and evaluation. The planning stage includes coordination between the team and the village as well as the provision of materials and the readiness of fish feed processing practices. Implementation includes the provision of material, discussion and practice of the process of making fish feed. The evaluation stage includes reviewing the activities of the fish feed manufacturing process, providing input and directing activities that can be carried out further in order to increase production. Results: Service activities start from the preparation of activities to the implementation of activities. In the preparation of the activity, the team ensured that there were practical materials for making fish feed imported from Malang. Before practicing, the team first explained the importance of fish farming in ponds. To obtain the desired results of fish cultivation, the team also provides knowledge about making fish feed to the participants of service activities. In the discussion of making fish feed, the servant conveyed about the stages in the process of making fish feed such as the flouring process, weighing ingredients, mixing, molding and drying pellets. Farmers in Wangen Village tend to like the use of floating fish feed because the fish will be visible when taking the distributed feed. Conclusion: Service activities have a positive impact on training participants. Participants know that good fish feed is not because it is expensive, but because of the content and nutritional needs needed by fish for the growth process. The process of feeding in ponds is not arbitrary, but one must know about the age of the fish, the state of the water and the environment of the pond, not from giving too much food and the fish mill grow bigger faster With the cooperation between farmer groups and BUMDES in the  production and sales process, training on packaging manufacture, permit management and sales and administration systems. Suggestion:. Further service activities that can be done are devotion about bookkeeping and fish feed marketing science